A new clinical challenge: supporting patients coping with the long-term effects of COVID-19. Issue 4 (2nd October 2022) - Goldberg, Neal C.; Poirier, Sabrina; Kanas, Allison; McCorkell, Lisa; McGinn, Carrie Anna; Re'em, Yochai; Kuehnel, Kathi; Muirhead, Nina; Ruschioni, Tahlia; Taylor-Brown, Susan; Jason, Leonard A.
ABSTRACT: Mental Health Practitioners (MHPs) have a unique opportunity to provide resources and support to those suffering from Long COVID (LC), the post infectious illness that often follows an acute SARS-CoV-2 infection. In working with these individuals, MHPs can learn from the experiences of patients with another post-infectious disease known as myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). ME/CFS was once thought to be a psychologically mediated disorder caused by deconditioning and the fear of exertion following a precipitating event such as a viral infection. Research now shows that LC and ME/CFS are biomedical, multisystem, complex physiologic diseases. This article provides a framework to MHPs for the treatment of LC patients using knowledge derived from three decades of research on ME/CFS.